Extracellular vesicles: Targeting the heart - Yin, Xin; Jiang, Li-Hong (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases rank the highest incidence and mortality worldwide. As the most common type of cardiovascular diseases, myocardial infarction causes high morbidity and mortality. Recent studies have revealed that extracellular vesicles, including exosomes show great potential as a promising cell-free therapy for the treatment of myocardial infarction. However, low heart-targeting efficiency and short plasma half-life have hampered the clinical translation of extracellular vesicles therapy. Currently, four major types of strategies aiming at enhancing target efficiency have been developed, including modifying EVs surface, suppressing non-target absorption, increasing uptake efficiency of target cells and utilizing the hydrogel patch. This presented review summarizes current researches aim at EVs heart-targeting and discuss the challenges and opportunities in EV therapy, which will be beneficial for the development of effective heart-targeting strategies.